HUBUNGAN DUKUNGAN KELUARGA DENGAN BODY IMAGE PADA PASIEN KANKER PAYUDARA YANG MENJALANI KEMOTERAPI DI RUANGAN POLI KLINIK ONKOLOGI RSUD PROF. DR. W. Z. JOHANNES KUPANG - Mirna Rosvita Elfeto; Sebastianus Kuriniadi Tahu; Istha Leanni Muskananfola (CHMK Applied Science Journal, 2022)
ABSTRACT Breast cancer is a disease that occurs due to excessive growth or uncontrolled development of cells or breast tissue. Breast cancer sufferers experience many changes in themselves and their daily lives which include physical and psychological conditions such as pain, fatigue, sleep rest. There are also psychological changes such as appearance, body image, positive feelings and negative feelings. Patients with a positive body image in undergoing treatment will experience the growth of new tissue or cells that have died during chemotherapy whyle patients with a negative body image will experience severe depression and can accelerate the growth of breast cancer and have an impact on death. This study aims to determine the relationship between family support and body image in breast cancer patients undergoing chemotherapy in the oncology clinic of the hospital. Prof. Dr. W. Z. Johannes Kupang. This research is a quantitative research using corelation analytic research design and research design gross sectional the sample in this study was 77 people selected by porposive sampling hole collection data using a questionnaire. The results of the statistical test using Spearman Rho shows (p:0.000) with correlation cofficient 0.794 which means that there is a relationship between family support and body image in breast cancer patients undergoing chemotherapy, in the positive category with a strong correlation. Strength, from the results of this study, it is hoped that good family support must be maintained in order to improve a good body image. Keywords: Family Support, Body Image, Breast Cancer, Chemotherapy